2007
DOI: 10.1007/s10608-006-9109-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personal Standards in Clinically Significant Perfectionism. A Person-Oriented Approach to the Study of Patterns of Perfectionism

Abstract: Clinically significant perfectionism is defined as patterns of perfectionism which are over-represented in clinical samples and under-represented in non-clinical samples. The present study contrasted two hypotheses about what characterizes clinically significant perfectionism: the two-factor theory and perfectionism/acceptance theory. First, a person-oriented approach by means of cluster analysis was used to identify typical patterns of perfectionism. These clusters were then cross-tabulated with two clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…Not only did personal standards predict less fear of experiencing shame and embarrassment, they also predicted more positive affect after failure. As such, it is important to distinguish between perfectionistic strivings and perfectionistic concerns and to recognize that the former can be adaptive and healthy only when athletes accept their imperfections (i.e., failures, mistakes, shortcomings; Lundh, Saboonchi, & Wångby, 2008). Conversely, perfectionistic strivings can be unhealthy and maladaptive when athletes "turn striving for perfection into a demand for perfection" and are unable to accept imperfection (Lundh et al, 2008, p. 255), and when their self-worth is contingent on achieving perfection (DiBartolo, Frost, Chang, LaSota, & Grills, 2004;Dunkley, Zuroff, & Blankstein, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Not only did personal standards predict less fear of experiencing shame and embarrassment, they also predicted more positive affect after failure. As such, it is important to distinguish between perfectionistic strivings and perfectionistic concerns and to recognize that the former can be adaptive and healthy only when athletes accept their imperfections (i.e., failures, mistakes, shortcomings; Lundh, Saboonchi, & Wångby, 2008). Conversely, perfectionistic strivings can be unhealthy and maladaptive when athletes "turn striving for perfection into a demand for perfection" and are unable to accept imperfection (Lundh et al, 2008, p. 255), and when their self-worth is contingent on achieving perfection (DiBartolo, Frost, Chang, LaSota, & Grills, 2004;Dunkley, Zuroff, & Blankstein, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In our view, there are three approaches from theory and research in clinical psychology that seem promising in this regard, and that could readily be adopted in to the sporting context. The first approach is based on perfectionism/acceptance theory (Lundh, 2004) which holds that perfectionistic strivings are adaptive when combined with the acceptance of imperfections (i.e., failures, mistakes, shortcomings) (Lundh et al, 2008). According to Lundh (2004), perfectionistic strivings are not unhealthy or dysfunctional as such.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies yielded further evidence for the existence of these three perfectionism profiles (e.g., see Rice & Ashby, 2007 for an overview), although at least some studies found evidence for more than three clusters (e.g., Lundh, Saboonchi, & Wangby, 2008). Further, these studies showed that the clusters had distinct profiles in terms of different outcome variables, such as depression, self-esteem, anxiety, and positive affect (Rice & Ashby, 2007).…”
mentioning
confidence: 99%